Analysis of difficulties presented by university students in basic mathematics - Soto Quiroz, Roger Iván (2020)
This article aims to analyze the different difficulties, both academic and attitudinal, that are presented in university students who take the Basic Mathematics course for second time. This work is a qualitative research, with phenomenological design, with application of the unstructured interview technique. The theoretical support is based on reading comprehension, school skills, meaningful learning, quantitative reasoning and attitudes towards mathematics. The sample was made up of 10 students who take the Basic Mathematics course for the second time: 03 of the Professional Graphic Design career, 03 of Interior Design and 04 of Fashion Design and Management; 03 teachers who teach the course and 05 academic tutors who carry out academic tutoring activities and workshops to reinforce the course. The results allowed us to affirm that they discovered six difficulties: 1) Difficulty in reading comprehension of mathematical problems, 2) difficulty in understanding basic mathematical contents, 3) difficulty with attending classes, 4) difficulty in interest and motivation for the course , 5) difficulty in reviewing mathematical topics, 6) difficulty in attending tutoring and reinforcement workshops.